2022
DOI: 10.1080/12298093.2022.2158557
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Thymol against Aspergillus awamori and Botrytis aclada Isolated from Stored Onion Bulbs

Abstract: The antifungal activity of thymol against Aspergillus awamori F23 and Botrytis aclada F15 in onions was examined through direct treatment with amended media and gaseous treatment with I-plates (plastic plates containing central partitions). The protective and curative control efficacy of thymol was examined 24 h before and after the inoculation of onion bulbs with the fungal isolates. Mycelial growth, sporulation, and spore germination of the isolates were inhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Thymol had greater efficacy than eugenol, and at 360.0 µg mL -1 , thymol completely inhibited germination of N. parvum and D. seriata conidia. A lower thymol concentration (100.0 µg mL -1 ) was sufficient to reduce F. oxysporum spore germination by 80% (Liu et al, 2022), and 100% inhibition was achieved by Oh et al (2022) for Botrytis aclada conidia. Their study also reported that Aspergillus awamoris conidia were resistant to thymol, and only treatment with 500 µg mL -1 completely inhibited germination.…”
Section: Discussionmentioning
confidence: 96%
“…Thymol had greater efficacy than eugenol, and at 360.0 µg mL -1 , thymol completely inhibited germination of N. parvum and D. seriata conidia. A lower thymol concentration (100.0 µg mL -1 ) was sufficient to reduce F. oxysporum spore germination by 80% (Liu et al, 2022), and 100% inhibition was achieved by Oh et al (2022) for Botrytis aclada conidia. Their study also reported that Aspergillus awamoris conidia were resistant to thymol, and only treatment with 500 µg mL -1 completely inhibited germination.…”
Section: Discussionmentioning
confidence: 96%